PROGRESSIVE IDEAS OF PROFESSIONAL TRAINING OF FUTURE MASTERS OF ELEMENTARY EDUCATION TO INNOVATIVE ACTIVITIES IN FOREIGN COUNTRIES - Tsiuniak, Oksana (Mountain School of Ukrainian Carpaty, 2020)
Today, Ukrainian society needs professionals with innovative thinking and a keen desire to implement their ideas in social life, driven by information, economic, social, political, cultural and religious processes of the third millennium. The modern world requires young people to be able to respond efficiently and promptly to innovative changes that are taking place in society, to be self-sufficient, proactive, responsible citizens, successful people, that is, professionally competent. That is why the problem of effective professional training of future specialists is an urgent one, which will be able to easily adapt to the changing conditions of today and be competitive in the labor market. The urgency of the problem with the professional training of future masters of elementary education to innovative activities is substantiated in the article. The general education system tendencies of the leading countries in the European Union, in particular, France, Denmark, Germany, England, that in recent years have collected positive experience in reforming important parts of the future teacher's education system, have been clarified. It is worth noting that Ukrainian educators are actively studying and using foreign experience in training teachers in European countries, the United States and Finland. The progressive ideas and features of future teachers’ training in different countries, which can be introduced for domestic education, are established. In the publication it is emphasized that the study provides for the feasibility of studying the foreign countries experience in the training of future masters of elementary education to innovative activity.